Integrated Marketing Communication Model in Shaping Brand Equity and Business Performance in the Creative Industries of Embroidery Sector - Maman Sulaeman; Hasan Fahmi Kusnandar (Budapest International Research and Critics University, 2020)
At this time, competition in the business world is getting tighter, no exception with the embroidery industry. In order to survive in the middle of the competition, they must have the right marketing communication strategy. Marketing communication plays a very important role for marketers. Without communication, consumers and society as a whole will not know the existence of products in the market. This research aims to analyze the integrated marketing communication model in shaping brand equity and business performance in the embroidery industry in Tasikmalaya Regency. The research method used is descriptive causality, by creating a description or description systematically, factually and accurately about the fact or nature of the object and interpreting the relationship between the phenomena investigated. The population of this research is the owner of the embroidery industry in Tasikmalaya of 949 people, sampling in this study is using accidental sampling method obtained 150 people. The results showed that partially and simultaneously direct marketing, personal selling, sales promotion, public relations and advertising on purchasing decisions and impact on business performance. Market attractiveness in addition to influencing purchasing decisions is also very potential to increase market share and growth of a company's business performance.